CDYL Deficiency Disrupts Neuronal Migration and Increases Susceptibility to Epilepsy - Rui Qin; Shuai Cao; Tianjie Lyu; Cai Qi; Weiguang Zhang; Yun Wang (Cell Reports, 2017)
Summary: During brain development, the correct migration of newborn neurons is one of the determinants of circuit formation, and neuronal migration defects may lead to neurological and psychiatric disorders. The molecular mechanisms underlying neuronal migration and related disorders are poorly understood. Here, we report that Chromodomain Y-like (CDYL) is critical for neuronal migration in mice. Knocking down CDYL caused neuronal migration defects and disrupted both mobility and multipolar-to-bipolar transition of migrating neurons. We find that CDYL regulates neuronal migration by transcriptionally repressing RhoA. In addition, CDYL deficiency increased the excitability of cortical pyramidal neurons and the susceptibility of mice to convulsant-induced seizures. These results demonstrate that CDYL is a regulator of neuronal migration and shed light on the pathogenesis of seizure-related neurodevelopmental disorders. : Qin et al. find that CDYL plays a role in neuronal migration by repressing RhoA transcription. CDYL deficiency leads to increased excitability of cortical pyramidal neurons and susceptibility to epilepsy in mice. Keywords: CDYL, neuronal migration, transcription, RhoA, epilepsy